Since \( S \) varies directly as the \( \frac{3}{5} \) power of \( T \), we can express this relationship as:
\[ S = k \cdot T^{\frac{3}{5}} \]
where \( k \) is a constant.
We know that \( S = 24 \) when \( T = 32 \). We can use this information to find the constant \( k \).
Substituting the values into the equation:
\[ 24 = k \cdot (32)^{\frac{3}{5}} \]
Next, we need to calculate \( (32)^{\frac{3}{5}} \):
-
Calculate \( 32^{\frac{1}{5}} \): \[ 32^{\frac{1}{5}} = 2 \] (since \( 2^5 = 32 \))
-
Now raise it to the 3rd power: \[ (32^{\frac{1}{5}})^{3} = 2^3 = 8 \]
Now substitute back into the equation:
\[ 24 = k \cdot 8 \]
To find \( k \):
\[ k = \frac{24}{8} = 3 \]
Now we have the relationship:
\[ S = 3 \cdot T^{\frac{3}{5}} \]
Next, we want to find \( S \) when \( T = 243 \):
\[ S = 3 \cdot (243)^{\frac{3}{5}} \]
To calculate \( (243)^{\frac{3}{5}} \):
-
Calculate \( 243^{\frac{1}{5}} \): \[ 243^{\frac{1}{5}} = 3 \] (since \( 3^5 = 243 \))
-
Raise it to the 3rd power: \[ (243^{\frac{1}{5}})^{3} = 3^3 = 27 \]
Now substitute back into the equation for \( S \):
\[ S = 3 \cdot 27 = 81 \]
So, when \( T = 243 \), \( S \) equals \( \boxed{81} \).